Mesin Pemotong Keripik Tempe Dengan Metode Geser Untuk Meningkatkan Kualitas Dan Kuantitas Hasil Produksi - Sukroni; Tito Endramawan; Felix Dionisius; Mohammad Azwar Amat (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Tempe chips are a type of processed food made from soy tempeh which is fried thinly and mixed with spices and other ingredients. The Tempe Chips UMKM "Ocien" which is located on the Bandung-Palimanan Highway, Gempol Village, Gempol District, Cirebon Regency, West Java, is a producer of tempe chips with modern packaging. The problem faced is the result of cutting tempeh chips which have many defects, thereby reducing quality. Based on these problems, it isnecessary to design and manufacture a tempe chip cutting machine using the shearmethod and equipped with a cutting thickness control driven by an electric motor with a power of 0.25 HP. Tempe chip cutting machine has a length specification of80 cm, width 67 cm, height 83 cm. The process of making this machine includes image identification, preparation of tools and materials, fabrication (marking, cutting, welding, grinding). Tempe chip cutting machine has the capacity to cut 2 tempeh sticks with a length of 22 cm and a diameter of 5 cm. It can cut 440 slices with a thickness of 1 mm in 4 minutes, 294 slices in 1.5 mm thickness in 3 minutes,216 slices in 2 mm thickness. 2 minutes.